TELFest: an approach to encouraging the adoption of educational technologies - Farzana Latif (Association for Learning Technology, 2017)
Barriers to technology adoption in teaching and learning are well documented, with a corresponding body of research focused on how these can be addressed. As a way to combine a variety of these adoption strategies, the University of Sheffield developed a Technology Enhanced Learning Festival, TELFest. This annual, week-long event, emphasises the role technology can play through an engaging learning experience which combines expert-led practical workshops, sharing of practice, discussions and presentations by practitioners. As the popularity of the event has grown and the range of topics expanded, a community of practice has organically coalesced among attendees, supporting the mainstream adoption of several technologies and helping to broaden educational innovation beyond isolated pockets. This paper situates TELFest within the technology adoption literature by providing details about TELFest, outlining the results of an investigation into the impact that it has had on attendees' teaching practice and summarising some of the limitations of the method along with reflections on how to address these limitations in the future.